Humoral Immune Response Diversity to Different COVID-19 Vaccines: Implications for the “Green Pass” Policy - Polvere, Immacolata; Parrella, Alfredina; Zerillo, Lucrezia; Voccola, Serena; Cardinale, Gaetano; D’Andrea, Silvia; Madera, Jessica Raffaella; Stilo, Romania; Vito, Pasquale; Zotti, Tiziana (Frontiers in Immunology, 2022)
In the COVID-19 pandemic year 2021, several countries have implemented a vaccine certificate policy, the “Green Pass Policy” (GPP), to reduce virus spread and to allow safe relaxation of COVID-19 restrictions and reopening of social and economic activities. The rationale for the GPP is based on the assumption that vaccinated people should maintain a certain degree of immunity to SARS-CoV-2. Here we describe and compare, for the first time, the humoral immune response to mRNA-1273, BNT162b2, Ad26.COV2.S and ChAdOx1 nCoV-19 vaccines in terms of antibody titer elicited, neutralizing activity and epitope-reactogenicity among 369 individuals aged 19 to 94 years old. In parallel, we also considered the use of a rapid test for determination of neutralizing antibodies as a tool to guide policy makers in defining booster vaccination strategies and eligibility for Green Pass. Our analysis demonstrates that the titer of antibodies directed towards the Receptor Binding Domain of SARS-CoV-2 Spike is significantly associated with age and vaccine type. Moreover, natural COVID-19 infection combined with vaccination results, on average, in higher antibody titer and higher neutralizing activity compared to fully vaccinated individuals without prior COVID-19. We also found that levels of anti-Spike RBD antibodies are not always strictly associated to the extent of inhibition of RBD-ACE2 binding, as we could observe different neutralizing activities in sera with similar anti-RBD concentrations. Finally, we evaluated the reactivity to four synthetic peptides derived from Spike protein on randomly selected serum sample and observed that, similarly to SARS-CoV-2 infection, vaccination elicits a heterogeneous antibody response with qualitative individual features. On the basis of our results, the use of rapid devices to detect the presence of neutralizing antibodies, even on a large scale and repeatedly over time, appears helpful in determining the duration of the humoral protection elicited by vaccination. These aspects and their implications for the Green Pass Policy are discussed.